Physical Water Quality and Intestinal Protozoa Contamination on Household Water in Ajung District, Jember Regency - Dicky Setiawan; Wiwien Sugih Utami; Laksmi Indreswari; Yunita Armiyanti; Bagus Hermansyah (Jember Medical Journal, 2022)
Intestinal protozoa infections are still a major health problem in worldwide. The prevalence of intestinal protozoa infections are relatively high in countries facing lack of safe drinking water and lack of suitable sanitation facilities. Lack of sanitation facilities, open defecation, and contamination of environmental feces can make water quality worse, both in terms of physically, chemically, and biologically. Physical water quality is poor when the household water used daily does not meet the standard parameters of the physical water quality standard. The purpose of this study was to determine the relationship between physical water quality and intestinal protozoa contamination in household water in Ajung District, Jember Regency. This type of research is an observational analytic study with a cross sectional research design. The research method used is the correlation method, namely the relationship between physical water quality and intestinal protozoa contamination in household water. The population in this study is household water in Ajung District, Jember Regency. Data analysis consisted of univariate analysis to see the distribution and percentage of temperature, total dissolves solid, color, odor, and intestinal protozoa contamination in household water, and then bivariate analysis using the Chi-square test to analyze physical water quality and intestinal protozoa contamination. The conclusion is there is a relationship between physical water quality and intestinal protozoa contamination in household water.